Word Building - a Strategic Approach to the Teaching of Phonics - Gunning, TG (Reading Teacher, 1995)
Keywords: dept.rdg; ⛔ No DOI found

Children’s Acquisition and Retention of Word Spellings - Dreyer, Lois G.; Luke, Stephen D.; Melican, Eileen K. (The Varieties of Orthographic Knowledge: II: Relationships to Phonology, Reading, and Writing, 1995)
Spelling is one of several important operations involved in the act of writing but until recently has received attention primarily in the applied domain. Orthographic abilities, because of their strong association with reading (e.g. Perfetti, 1985), are now of increasing interest to those who study the cognitive bases of literacy development. It is generally acknowledged that phonological processes underlie essential aspects of word recognition (Adams, 1990; Dreyer, 1989; Liberman, Shankweiler & Liberman, 1989; Stanovich, 1986; Wagner & Torgesen, 1987; Williams, 1986). An expanding body of research suggests that orthographic factors can account for a significant amount of variance in word recognition over and above phonological abilities (Cunningham & Stanovich, 1990; 1993; Dreyer, 1994; Stanovich & West, 1989; Stanovich, West & Cunningham, 1991).
Keywords: Orthographic Knowledge; Phonological Awareness; Receptive Vocabulary; Target Word; Word Reading; dept.rdg

Cognitive profiles of reading-disabled children: comparison of language skills in phonology, morphology, and syntax: - Shankweiler, Donald; Crain, Stephen; Katz, Leonard; Fowler, Anne E; Liberman, Alvin M; Brady, Susan; Thornton, Rosalind; Lundquist, Eric; Dreyer, Lois G; Fletcher, Jack M; Stuebing, Karla K; Shaywitz, Sally E; et al. (Psychological Science, 1995)
A comprehensive cognitive appraisal of elementary school children with learning disabilities showed that within the language sphere, deficits associated with reading disability are selective: Phonological deficits consistently accompany reading problems whether they occur in relatively pure form or in the presence of coexisting attention deficit or arithmetic disability. Although reading-disabled children were also deficient in production of morphologically related forms, this difficulty stemmed in large part from the same weakness in the phonological component that underlies reading disability. In contrast, tests of syntactic knowledge did not distinguish reading-disabled children from those with other cognitive disabilities, nor from normal children after covarying for intelligence.
Keywords: dept.rdg